An Investigation of the Adaptation of Turkish Textile Enterprises to Industry 4.0 - Ahmet Özbek; Aytaç Yıldız; Mehmet Asif Alan (Acta Infologica)
Industry 4.0 is a new understanding of production and is based (to a great extent) on the removal of people from production by radically changing the understanding of people-oriented production – a concept that has dominated for a long time. This understanding is becoming more widespread day by day and it is predicted that the future will mean a better understanding of production. Therefore, it is anticipated that adaptation to this understanding will be one of the determining factors in the future success of enterprises. In this study, it was aimed to investigate the adaptation of textile companies operating in Turkey to Industry 4.0. Within the scope of the study, a questionnaire was prepared to analyze the perspectives of textile companies towards industry 4.0 and their expectations from the industry 4.0 technologies they use. The questionnaire was applied to 67 textile companies that ranked in the top 500 large enterprises of the Istanbul Chamber of Industry (ISO) in 2017 and 2018 and the data obtained were analyzed. According to the results of the analysis it was determined that the technology that businesses use the most is ERP. Due to the high investment cost, it has been determined that only half of enterprises invest in industry 4.0 technologies, that they believe that industry 4.0 is applicable in the textile industry, that to invest in these technologies will increase productivity and reduce costs, and as a result, the highest increase in efficiency will be achieved.